2002
DOI: 10.1159/000064763
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Growth in Cystic Fibrosis

Abstract: Malnutrition is a common complication of chronic diseases in children and may lead to growth impairment (stunting). Malnutrition in cystic fibrosis (CF) results from increased energy expenditure, decreased energy intakes, malabsorption of ingested nutrients because of pancreatic insufficiency and chronic inflammation. Malnutrition and high levels of inflammatory cytokines affect IGF-1 production through interrelated mechanisms. Nutritional support was shown to improve both nutritional status and outcome in CF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Since these activities involve building up muscle mass, specific care to ensure adequate nutrition should be taken with these patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since these activities involve building up muscle mass, specific care to ensure adequate nutrition should be taken with these patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Study of mice with a neuronspecific deletion of Cftr would help elucidate the role of neuronal Cftr. Second, chronic inflammation may also contribute to growth retardation in CF (7). There is evidence that CF patients have elevated systemic cytokines (37,38) and CF mice have elevated expression of inflammatory mediators in the intestine (39).…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%
“…In the pancreas, activation of Ca 2ϩ signaling by G protein-coupled receptors (GPCRs) 1 plays a central role in digestive enzyme secretion (3). Abnormal enzyme secretion can lead to numerous diseases, including malnutrition in cystic fibrosis (4) and, more commonly, acute pancreatitis (5). Several studies have shown a strong association between aberrant Ca 2ϩ signaling and pancreatitis (6 -8).…”
Section: Camentioning
confidence: 99%